ARCA BERCORAK SIWAISTIS DI KOTA DENPASAR, BALI - I Wayan Sumerata; Dewa Gede Yadhu Basudewa (Balai Arkeologi Bali, 2016)
This research aims to reconstruct the cultural history, and to describe the cultural change of human in the past, and also to provide data regarding the history of figurine art development, particuarly figurine with sivaistic features, in Denpasar. Data were collected through observation, interview, and literature study, and analyzed using qualitative and iconographic analysis. The result of this research shows that figurines with sivaistic features in Denpasar are distributed in ten religious places. The types of figurines which have sivaistic features are Durga, Ganesha, lingga-yoni, lingga, yoni, priest figurine, and Nandi. Up to now, those figurines are still used for religious activities, and as media to connect with God. Penelitian ini bertujuan untuk merekonstruksi sejarah kebudayaan, dan menggambarkan proses perubahan budaya manusia masa lampau, serta memberikan sumbangan data mengenai sejarah perkembangan seni arca, khususnya yang bercorak Siwaistis, di Kota Denpasar. Pengumpulan data menggunakan metode observasi, wawancara, dan studi kepustakaan, serta dianalisis menggunakan analisis kualitatif dan ikonografi. Hasil penelitian menunjukkan bahwa arca bercorak Siwaistis di Kota Denpasar tersebar pada sepuluh tempat suci. Jenis arca bercorak Siwaistis yang ditemukan adalah arca Dewi Durga, arca Ganesha, lingga-yoni, lingga, yoni, arca pendeta, dan arca Nandi. Sampai saat ini, arca-arca tersebut masih difungsikan dan dimanfaatkan untuk kegiatan keagamaan, sekaligus sebagai media untuk menghubungkan diri kepada Tuhan Yang Maha Esa.